OPTIMIZING PIGMENT PRODUCTION FROM PENICILLIUM SP. FOR SUSTAINABLE SILK DYEING - Naaz, Shumaila; Gupta, Charu; Aggarwal, Sunita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the use of microbial pigments from Penicillium sp. as a sustainable alternative to synthetic dyes in textile dyeing, focusing on optimizing pigment production and assessing color fastness on silk. Static Potato Dextrose Broth (PDB) at 28°C produced the highest concentration of red pigment after 27 days of incubation, with an optical density (O.D) of 1.010 at λmax = 530 nm. In contrast, 15°C resulted in slower pigment production (O.D = 0.860), and 37°C showed negligible growth. Adjusting the PDB pH to 5 increased pigment yield, aligning with previous studies showing Penicillium sp. thrive in acidic conditions. The final broth pH decreased to 4.0 due to organic acid production by the fungus. Silk samples dyed with these pigments were evaluated for color strength and fastness. The colorimetric values indicated moderate color intensity (K/S = 4.25) with a bright, pastel-like appearance (L* = 81.23), and a warm reddish-yellow hue (a* = 9.23, b* = 6.48). Fastness tests showed excellent performance for dry rub (rating 5), good results for wet rub (rating 4), and favorable wash fastness (rating 4 for staining and color change). However, light fastness was lower, suggesting potential fading under prolonged exposure. Overall, the study identifies Penicillium sp. as a promising source of natural dyes for silk, with optimized fermentation conditions (PDB, 28°C, pH 5, 27 days) leading to high pigment yield and strong fastness performance, offering a sustainable alternative to synthetic dyes in textiles.